Assessment of methods to study the acoustic properties of heterogeneous perforated panel absorbers. (April 2018) - Carbajo, J.; Ramis, J.; Godinho, L.; Amado-Mendes, P.
Abstract: Heterogeneous perforated panels are of great interest as sound absorbers, while achieving a smart high-end decoration in meeting rooms, showrooms, conference halls, etc. However, their uneven nature may pose a difficulty when trying to predict their acoustic performance using traditional impedance models. This work explores the use of four different methodologies: Admittance Sum Method, Parallel Transfer Matrix Method, Equivalent Circuit Method and Finite Element Method, together with the Johnson-Champoux-Allard (JCA) model, to estimate the acoustic properties of heterogeneous perforated panels. The proposed approaches were compared in terms of the computed sound absorption curves for different absorber arrangements. Even though the above methodologies exhibit a good agreement on the predictions, it was found that special attention must be paid to the type of backing cavity configuration (isolated or non-isolated) to yield correct results. Additionally, equivalent circuits for configurations with multiple cavity depths were proposed and their sound absorption also analyzed. In general, preliminary results show that these methodologies may be useful in the design stage of such devices.